2011
DOI: 10.1111/j.1526-4637.2011.01205.x
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Incisional Analgesia with Intravenous or Subcutaneous Infiltration of Ketamine Reduces Postoperative Pain in Patients after Open Cholecystectomy: A Randomized, Double-Blind, Placebo-Controlled Study

Abstract: A 2 mg/kg dose of subcutaneous infiltration ketamine or 1 mg/kg dose of intravenous ketamine given at approximately 15 minutes before surgery provides an adjunctive analgesia during 24 hours after surgery in patients undergoing cholecystectomy surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
33
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 37 publications
3
33
0
Order By: Relevance
“…Our study showed that intravenous and subcutaneous administration of low dose ketamine reduced not only the post-operative pain score, but also analgesic requirement after tonsillectomy. The results of previous studies in adults using low dose intravenous ketamine preemptively, demonstrated decreased pain scores and also reduced postoperative analgesic requirement (9,10,17). Although, the route and the time of the drug administration were different, still the results are contradictory regarding preemptive effects (7).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Our study showed that intravenous and subcutaneous administration of low dose ketamine reduced not only the post-operative pain score, but also analgesic requirement after tonsillectomy. The results of previous studies in adults using low dose intravenous ketamine preemptively, demonstrated decreased pain scores and also reduced postoperative analgesic requirement (9,10,17). Although, the route and the time of the drug administration were different, still the results are contradictory regarding preemptive effects (7).…”
Section: Discussionmentioning
confidence: 84%
“…Preschool patients are affected from undesirable effects of postoperative pain more than adults (8). It has been shown that using ketamine in children, as an analgesic could reduce the consumption of other analgesic drugs such as opioids, leading to fewer adverse effects (7,9,10). Both interception of nociceptive input and blockage of N-methyl-d-aspartate (NMDA) activation may be necessary for preventive analgesia.…”
Section: Introductionmentioning
confidence: 99%
“…Ketamine has been used to reduce post-operative pain following various surgical procedures like hernioraphy [20], abdominal hysterectomy [21], thoracotomy [22], circumcision [23], cesarean section [24], open cholecystectomy [25], appendectomy [26], tonsillectomy [27][28][29][30][31]. Recently ketamine has been used in oral and maxillofacial surgical practice as well [14,[32][33][34][35][36].…”
Section: Discussionmentioning
confidence: 99%
“…Atashkhoyi et al [24] evaluated the efficacy of pre-incisional subcutaneous infiltration of low-dose ketamine at the site of incision after cesarean section and reported decreased postoperative pain scores with a significant decrease of analgesics consumption. Safavi et al [25] concluded that a 2 mg/kg dose of Fig. 3 Comparision of mouth opening between Test group and Placebo group subcutaneous infiltration ketamine or 1 mg/kg dose of intravenous ketamine given at approximately 15 min before surgery provides an adjunctive analgesia for 24 h after surgery in patients undergoing cholecystectomy surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation